Owners’ Portfolio Diversification and Firm Investment - Lyandres, Evgeny; Marchica, Maria-Teresa; Michaely, Roni; Mura, Roberto (Review of Financial Studies, 2019)
Abstract Portfolio diversification of firms’ controlling owners influences their firms’ capital investment. Empirically, the effect of owners’ portfolio diversification on their firms’ investment levels is positive for publicly traded firms and tends to be negative for privately held ones. These findings are consistent with predictions of a model in which a risk-averse investor simultaneously chooses her portfolio structure, and both the level and riskiness of capital investment of the firm she controls, and in which the firm can be potentially constrained in its capital investment choices. Overall, our results indicate that owners’ portfolio underdiversification and firms’ financial constraints can affect firms’ resource allocation. Received May 3, 2017; editorial decision March 8, 2019 by Editor Francesca Cornelli. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.